Analysis of community knowledge and behavior towards plastic waste pollution control in the coastal area of Banyuwangi Regency, Indonesia - Sulistyorini, Lilis; Abualreesh, Muyassar Hamid; El- Regal, Mohamed Ahmed Ali Abu; Mohd Elias, Saliza; Azizah, R.; Lutpiatina, Leka; Arfiani, Novi Dian; Rizaldi, Muhammad Addin; Jannah, Ratih Zahratul; Santanunurti, Muhammad Browijoyo (Elsevier B.V., 2025)
Banyuwangi in East Java, Indonesia was one of the districts that had the potential to produce an alarming quantity of plastic waste. The local government held a Zero Waste-Based Plastic Waste Pollution Control Facility to overcome plastic waste issues. This research aimed to analyze the effect of Zero Waste-based plastic waste pollution control on the potential for plastic waste pollution in the community of the coastal areas of Banyuwangi Regency, Indonesia. The research was conducted on the coastal areas within four sub-districts in Banyuwangi Regency, namely Muncar, Banyuwangi, Kalipuro and Blimbingsari. A total of 636 respondents were recruited. A set of questionnaires was used to obtain data for knowledge, attitude, action, pollution control and pollution potential of plastic waste. All data was analyzed using SPSS software. Respondents had sufficient knowledge (88.8 %) but lacked good attitude (65.6 %) toward plastic waste. Respondents' behavior and knowledge needed improvement, as 38.85 % of respondents were not well informed about plastic waste. Knowledge, attitudes and actions of respondents showed no influence on the potential for plastic waste pollution. The control of plastic waste through Zero Waste-Based Plastic Waste Pollution is influential on the potential for plastic waste pollution along the coast of Banyuwangi Regency. It is necessary to provide Zero Waste-Based Plastic Waste Pollution facilities and increase community awareness in order to minimize pollution of marine waters, particularly due to plastic waste.